2010
DOI: 10.1021/nn102187v
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplex Delivery of siRNA and Prodrug Enzyme for Multimodality Image-Guided Molecular Pathway Targeted Cancer Therapy

Abstract: The ability to destroy cancer cells while sparing normal tissue is highly sought after in cancer therapy. Small interfering RNA (siRNA)-mediated silencing of cancer-cell specific targets, or the use of a prodrug enzyme delivered to the tumor to convert a non-toxic prodrug to an active drug are two promising approaches in achieving this goal. Combining both approaches into a single treatment strategy can amplify selective targeting of cancer cells while sparing normal tissue. Noninvasive imaging can assist in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 46 publications
(95 reference statements)
1
75
0
Order By: Relevance
“…The uracil phosphoribosyl transferase (UPRT) gene from Escherichia coli encodes uracil phosphoribosyltransferase, which converts uracil and 5-phosphoribosyl-1-R-diphosphate to uridine monophosphate (UMP). This protein is a potential target in cancer therapy, but not present in mammalian genomes when combining with UPRT (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The uracil phosphoribosyl transferase (UPRT) gene from Escherichia coli encodes uracil phosphoribosyltransferase, which converts uracil and 5-phosphoribosyl-1-R-diphosphate to uridine monophosphate (UMP). This protein is a potential target in cancer therapy, but not present in mammalian genomes when combining with UPRT (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Breton and colleagues performed a study using a modified Ankara virus to express yeast CD in situ, reducing tumor growth in a glioblastoma mouse model (10). After introducing a viral vector for in vitro transformation of several cancer cell lines (12,31) and evaluation in preclinical models (32) not detected significant immunogenicity of bCD in animals (33,34). We do not anticipate that bCD 1525 would have immunogenic properties different from those of the regular protein, but this should be evaluated before translation to human use.…”
Section: Discussionmentioning
confidence: 99%
“…future science group Review Shahbazi, Ozpolat & Ulubayram ously reported that tumor doubling time was reduced threefold with bCD only and sixfold with siRNA-and bCD-containing nanoplexes together with a single dose of 5-fluorocytosine [186].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%